Public perception of forest crimes: the case of Ilgaz Province in Turkey - Ünal, Hasan Emre (Crime, law and social change, 2021)
The protection and sustainable management of forests are widely accepted and considered a solution for mitigating climate change. Although there are many variables concerning economic, political, social, and legal aspects in terms of forest protection, the main target is always focused on human behavior. Legal instruments are one of the most effective methods in regulating human behavior. Since illegal activities are often the most destructive human behavior, this study aims to examine the public’s perception regarding forest crimes: illegal logging, illegal transportation/smuggling, open land expansion, squatting, and arson. It has been explained in previous studies that legal regulations alone do not sufficiently prevent forest crimes. Although forest villagers themselves benefit greatly from healthy forests, it was determined that occurrences of criminal activity in forests are directly correlated with low-income levels, lack of awareness of laws and sanctions, low penalties on crimes, and a low level of education. Those administrations responsible for the management of forests need to identify the socio-economic needs of these groups and communities through social analysis within the parameters of SFM.